Chronology of Deciduous Teeth Eruption: Agreement between Classic Authors - Lorena Ferreira (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2015)
Objective: Assessing agreement between the erupti on age of deciduous teeth eruption (DTE) in a children sample the City of Vitoria , Brazil, and the eruption age reported by classical authors. Material and Methods: The data derive from a cohort study with 86 newborns until their 36th month of age. Averag e DTE age of each child was calculated and testing was performed to comparing DTE age described by classic authors. Then, kappa test, McNemar and prevalence adjusted kappa were applied. Results: Average DTE ranged between 8 and 29 months of age in the lowe r arch, and 11 to 30 months in the upper arch. There was higher agreement proportion for DTE age of 71/81 (kappa= 0.82; IC95%= 0.72 - 0.93) and 52/62 (kappa= 0.88; IC95%= 0.78 - 0.99) between Minot (1873) and Shour and Massler (1941). Followed by deciduous te eth eruption age between the latter author and Logan and Kronfeld (1939) for 51/61 and 55/65 and between Lunt and Law (1974) for 53/63 and 73/83. High McNemar values were found for DTE age of 51/61 (McNemar= 54.0; p= 0.000), 72/82 and 75/85 between Logan a nd Kronfeld (1939) and Lunt and Law (1974) and for 51/61 between the latter author and Shour and Massler (1941). Conclusion: The sequence of DTE found here was similar to that reported in several studies, as well as average eruption age of deciduous upper and lower central incisors. However, average age was always later for the other teeth. Levels of agreement were higher for deciduous incisor and canine eruption than for deciduous molars.